Mathematical modeling of adsorption for wastewater treatment - Ainihayati, Ismail (2012)
Textile industries produced huge volume of wastewater which is contains synthetic dyes.Synthetic dye is a toxic dye and can cause harm to the aquatic ecosystem as well as to human being because it is poisonous and have carcinogenic and mutagenic.Therefore,dyes must be removed from wastewater before discharged to the drain or river.The method which is widely used is adsorption because this method requires simple operation procedures,low cost compared to the other separation process and no sludge formation.The potential of tea dust as low cost adsorbent to remove color from dye solution was studied. The equilibrium and kinetic of adsorption were studied in batch mode and then mathematical model of adsorption for wastewater treatment was developed. The experiment was conducted under batch mode with various parameters such as initial concentration, pH, adsorbent dose and contact time.The equilibrium study,kinetic study and effect of pH and effect adsorbent dosage were conducted under batch mode constant temperature. The equilibrium data were fitted with Langmuir isotherm,Freundlich isotherms and modified Langmuir model while for kinetic data were fitted with pseudo-first-order,pseudo-second-order and Unified Approach model.Tea dusts have potential to adsorbed crystal violet very well when solution was basic.The adsorption data were fitted better in Langmuir Isotherm which mean this adsorption of crystal violet onto tea dust was monolayer system and the structurally homogeneous sorption surface of adsorbent.The Lagergren pseudo-first order and pseudo-second order were dependent on initial concentration and adsorbent dosages but the Unified Approach Model does not depend on this two parameters.Thus,Unified Approach Model was described the kinetic well and it was useful for modeling the adsorption of crystal violet using tea dust.